Histomorphological, Histochemical and Histoenzymic Studies on Lymphoid Tissue of Oropharynx in Khaki Campbell Breed of Duck (Anas platyrhynchos) - Gedam, P.M. (Indian Journal of Veterinary Anatomy, 2020)
In oropharynx, the lymphatic tissue was observed in three different forms, the diffuse, the solitary lymphatic nodules and lymphatic follicles. The solitary nodules were covered by collagen fibers. The network of the lymphatic tissue was formed by reticular fibers. The stratified squamous epithelium covering the follicles was modified to form lymphoepithelium. The distribution of lymphatic tissue was more or less similar in all age groups, but there was slight decline in the Gr. V. The PAS positive activity in the nodules of oropharynx in Gr. II,III and IV, was strong where as moderate activity was observed in Gr. I and Gr. V. Germinal centres showed strong activity in almost all the groups. The alkaline phosphatase activity in lymphatic nodules of oropharynx was mild to moderate in Gr. I and Gr. II birds. The moderate activity was observed in Gr. III, IV and V. The acid phosphatase activity was mild to moderate in the lymphatic nodules of the oropharynx in Gr. I and Gr. II birds.